The urea-creatinine ratio on the seventh day predicts the short-term prognosis of spontaneous intracerebral hemorrhage: a retrospective study - Xingguo Wu; Ningxiang Qin; Yiqi Zhang; Fahang Yi; Xi Peng; Liang Wang (PeerJ)
Background and Objectives This study aimed to investigate the association between hydration status and 90-day functional outcomes in patients with spontaneous intracerebral hemorrhage (SICH). Methods We conducted a retrospective analysis of 215 SICH patients admitted to the Neurology Department of the First Affiliated Hospital of Chongqing Medical University between January 2021 and September 2023. Demographic characteristics, imaging findings, and laboratory parameters were collected. Patients were stratified into good (modified Rankin Scale [mRS] ≤ 2) and poor (mRS > 2) prognosis groups based on 90-day outcomes. Results Univariate analysis revealed that poor prognosis was associated with advanced age, prolonged hospitalization, and elevated urea nitrogen/creatinine ratio (UCR) on day 7 (p < 0.05). Multivariate logistic regression identified three independent predictors of poor outcome: age (OR = 1.059, 95% CI [1.025–1.094], p < 0.01), Glasgow Coma Scale score (OR = 0.420, 95% CI [0.308–0.571], p < 0.01), and day-7 UCR (OR = 1.095, 95% CI [1.045–1.148], p < 0.01). Receiver operating characteristic (ROC) analysis demonstrated that day-7 UCR predicted poor outcomes with an area under the curve (AUC) of 0.72 (95% CI [0.643–0.789]), with an optimal cutoff value of 30.68. Patients with UCR ≤ 30.68 had significantly higher rates of favorable outcomes (75.2%) compared to those with UCR > 30.68 (37.9%). Conclusion Elevated blood UCR (>30.68) on day 7 post-SICH is an independent predictor of unfavorable short-term prognosis.